The Reliability of Balance Assessment Tests in Adolescent Athletes: A Systematic Review - Yojana, Egik; Azizah, Amalia Nur; Yahya, Muchammad (Annual Physiotherapy Scientific Meeting Proceeding, 2022)
Introduction: The growth spurt in adolescents is typically identified by peak skeletal growth rates, which resulted in different anatomical and physiological functions compared with adults, thus could affect the dynamic postural control and increasing the vulnerability to injury. However, the available balance assessment is mostly only applicable to adults, and the implementation for the adolescent population is still questionable; hence this study aims to identify the most reliable balance assessment for adolescent athletes. Methodology: A systematic review of reliability studies that were obtained from 5 electronic databases: PubMed, Scopus, Web of Science, EBSCOhost, and Ovid MEDLINE. The study article was assessed using the Quality Appraisal of Reliability Studies (QAREL) scale. Research findings: The initial search resulted in 753 articles, where five studies were then extracted and examined using the QAREL scale. These five studies consisted of three balance assessments, including Y-Balance Test in three studies, and the rest are Dual Task Postural Control Testing, and Tandem Gait Test. The highest score was 87.5% from a study by Greenberg et al., which assessed the Y-Balance Test. Conclusions: The most reliable balance assessment tool according to the QAREL scale was the Y-Balance Test.